Conflitos na adolescência: Uma avaliação dos alunos do 7° e 8° ano do ensino fundamental - Cascavel-PR - Wisniewski, Edirlene Doroti; Cristovam, Marcos Antonio da Silva; Osaku, Nelson Ossamu; Bresolin, Adriana Chassot; Gabriel, Gleice Fernanda Costa Pinto [UNESP]; Rover, Milene de Moraes Sedrez; da Silva, Fernanda Soares (My University, 2016)
Objective: Assess and characterize the confl icts characteristic of adolescence from 7th and 8th years students from primary education of four public institutions in Cascavel City- PR. Methods: cross-sectional study with application of questionnaire to students elementary school, enrolled and attending school in 2013 and who agreed to participate of the survey, with prior parental permission. Results: were applied 167 questionnaires to the students, of which 46% were males and 54% were females with ages between 12 to 14 years, where most were in 8th grade (56.3%). In the analysis of the issue “preoccupation”, 50% of the students point to the following topics (50%): pregnancy, STDs, homosexuality, AIDS, suicide, depression, tension, alcoholism, sexual abuse, stress, cigarette, food, feelings that scare, nervousness, generally violence, general diseases, obesity, drugs and death. On the issue of “orientation” (42.1%) pointed to: freedom in home, relationships with siblings, relationships with parents, friendships, school, marriage, work, dreams, religion, dating, masturbation, contraception, ejaculation, sexual relationship and menstruation. And on the category “doubt” (7.9%): occupational choice, political and timidity. Conclusion: In this study it was possible to elaborate a profi le of the adolescents in our community, most of which had 13 years old and were female, where the subject sexuality was the one generating most concern. The results can to help to promote individual and collective actions to solve the doubts, to prepare questions and to emphasize the role of schools in issues related to socio-emotional development of their students.
Conflicts in adolescence: An assessment of students from 7° and 8° grades of elementary school - Cascavel City - Paraná State
Keywords: Adolescent; Adolescent behavior; Surveys and questionnaires